Screaming Eagles 101st Airborne Division - Bryant, Russ, 1966-; Bryant, Susan (Military power, 2007)
Photographs and text provide an overview of the 101st Airborne Division's history, organization, training, and weapons; describing their role and usage during World War II, Operations Enduring and Iraqi Freedom, and combat missions in the Middle East; and profiling Medal of Honor recipients.